Business Model Canvas: Batik Frame Clip / Syaidatul Norifa Mohd Badrul - Mohd Badrul, Syaidatul Norifa (2020)
For my batik frame clip shop I started with the value propositions of adjustable frame, safety frame and easy to bring. After performing my customer surveys I was able to verify my assumptions that customers would like to have easy to bring and a safety product